The Glasgow prognostic score can be a predictor of mortality in acute exacerbation of chronic obstructive pulmonary disease - Kuluozturk, Mutlu; Devec, Figen (Taylor & Francis Ltd, 2020)
Aim: To determine the prognostic value of Glasgow Prognostic Score (GPS) in acute exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) requiring hospitalization. Methods: Hospital electronic database of 129 patients with AECOPD was retrospectively searched and CRP levels, complete blood count, arterial blood gas (ABG) values and pulmonary function test (PFT) parameters of patients were recorded. Hospital mortality and need for ICU transfer were determined as adverse outcomes from files of cases. Results: 106 of 129 patients were male (82.2%) and rest of them were female (17.8%). GPS 0 was not observed in any patient, GPS 1 was observed in 101 patients, and GPS 2 was observed in 28 patients. The rate of adverse outcomes (ICU/Ex) was significantly increased in the GPS 2 group when compared to the GPS 1 group (X-2:7.631, p < 0.01). Logistic regression analysis indicated that pH <= 7.35 (p < 0.05, OR: 5.65, CI: 1.35-23.58%) and GPS 2 score (p < 0.05, OR: 5.52, CI: 1.45-20.97%) were independent predictors for adverse outcomes for AECOPD. Conclusion: Our results demonstrate that the GPS may have predictive value for adverse outcomes in patients with AECOPD.
Keywords: COPD; acute exacerbation; mortality; need for intensive care unit